Women and depression - Guth, Jamie; Bonfield, Arlyn; Dartmouth-Hitchcock Medical Center; Aquarius Health Care Videos (United States : Aquarius Health Care Videos, 2000)
Women and their families talk about their experiences with depression and its treatment.
Editor, Robin Taylor.
Keywords: Depression in women -- Personal narratives; Depression in women -- Treatment